An Energy Efficient Modulation Scheme for Body-Centric Terahertz (THz) Nanonetworks - Vavouris, Apostolos K.; Dervisi, Foteini D.; Papanikolaou, Vasilis K.; Diamantoulakis, Panagiotis D.; Karagiannidis, George K.; Goudos, Sotirios K. (Technologies, 2019)
In body-centric communications, energy efficiency is a critical performance metric, while the achievable data rate is not of primary concern. In this paper we present a novel modulation scheme, which can be efficiently used in body-centric terahertz (THz) nanonetworks. The proposed scheme is a combination of the time-spread On-Off keying (TS–OOK) and the pulse position modulation (PPM) and presents lower energy consumption, compared to other existing methods as TS–OOK, at a minor cost to the data rate. Furthermore, another important aspect is that the proposed modulation scheme can be effectively used to mitigate the impact of the specific kind of noise in THz body-centric communications, thus leading to better error performance. Finally, we present analytical and simulation results in order to compare the new scheme with the existing TS–OOK.
Created from Fastlane, Scopus look-up
Keywords: body-centric communications; femtosecond pulses; nanonetworks; nanosensors; terahertz band